Millimeter Waves Hybrid Devices – Theory and Simulation - Odarenko, E. N.; Shmat'ko, A. A. (IEEE, 2002)
Hybrid mm waves O-type electron devices are considered. The multidimensional nonlinear self-consistent theory of beam-wave interaction in different stages of hybrid devices has been developed. Output characteristics of hybrid amplifiers for different values of input signal are calculated.
Keywords: hybrid electron device; millimeter waves; nonlinear theory; two-dimensional model